Penanaman Nilai Pendidikan Karakter Berwawasan Kebangsaan pada Mahasiswa Melalui Pembelajaran Menulis Artikel Ilmiah - Sabitul Kirom (Jurnal Ilmiah Wahana Pendidikan, 2020)
Cultivating the value of character education with a national perspective in students is very important today. This study aims to describe the implementation of the implementation of character education with a national perspective in students through learning to write scientific articles. The main focus of this research is: (1) learning design, (2) learning implementation, (3) and learning evaluation. The method used is a qualitative research method. The results of this study are as follows. First, the lecturer has implemented the cultivation of the value of character education with a national perspective through learning to write scientific articles at the learning design stage. The value of character education is contained in the syllabus documents, RPS, RPP, and college contracts. Second, during the learning process the lecturer has implemented the value of character education with a national perspective. Third, at the learning evaluation stage, lecturers have instilled the value of character education with a national perspective. In evaluation activities, lecturers put forward the aspects of openness, tolerance, and honesty.